MENINGKATKAN TATA KRAMA PERILAKU SISWA MELALAUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA - Lusy Annuriya Ilhami; Gudnanto Gudnanto; Indah Lestari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This study aims to improve the behavioral etiquette of eleventh-grade TKR 4 students at SMK NU Ma'arif 1 Kudus through group guidance services utilizing sociodrama techniques. The background of this study is based on initial observations indicating that many students exhibit poor social etiquette in their interactions at school. Some of the problems identified include a lack of respect for peers and teachers, the use of impolite language, and behavior that does not conform to norms of politeness in the school environment. Sociodrama techniques are used as the primary approach in group guidance services because they allow students to understand and experience various social roles directly. Sociodrama is a learning method that involves role-playing specific social situations, in which students assume the role of individuals facing social conflict or moral dilemmas. Through this technique, students can explore their feelings, attitudes, and values in their social interactions. Furthermore, this technique also helps students develop empathy, communication skills, and social awareness in everyday life. This study used a qualitative approach, with subjects including eleventh-grade TKR 4 students experiencing etiquette issues. Data collection techniques included observation, interviews, and documentation to explore changes in student behavior during the service. The results showed that group guidance services using sociodrama techniques had a positive impact on improving student manners. Students who previously showed less respect for their peers and teachers showed changes in behavior, becoming more polite after participating in sociodrama sessions. They were also better able to position themselves in various social situations and understand the consequences of their actions. The conclusion of this study is that sociodrama techniques are an effective method in helping students develop better manners and social skills. Therefore, schools can consider implementing group guidance services using sociodrama techniques as part of their character education programs to improve the quality of students' social interactions.